Ảnh hưởng của nanocompozit CNT/ZnO đến khả năng bảo vệ của màng sơn polyuretan dưới bức xạ của tia tử ngoại - Vũ, Phạm Gia; Kim Cúc, Nguyễn Thị; Oánh, Vũ Kế; Trúc, Trịnh Anh; Xuân Hằng, Tô Thị (Vietnam Journal of Chemistry, 2016)
The deposition of ZnO on CNTs has been prepared by a sol–gel method. The CNT/ZnO nanocomposites synthesized were characterized by Fourier Transform Infrared (FTIR), X-ray diffraction (XRD) and scanning electron microscopy (SEM) methods. The analyses show that the nano ZnO deposition on CNT was crystalline in the form of hexagonal wurtzite structure. The average particle size of ZnO deposition on CNT is about 10 nm. The CNT/ZnO nanocomposites were incorporated into a polyurethane coating for improving the UV resistance of the coating. The Electrochemical Impedance Spectroscopy (EIS) measurement was performing during UV exposure for characterize the UV resistance of the coating. The corrosion resistance of polyurethane coatings containing 0.1 wt.% CNT/ZnO in UV radiation was higher than that polyurethane and polyurethane coatings containing CNT or ZnO at the same rate. Keywords. Carbon nanotube, nano ZnO, nano composite CNT/ZnO, polyurethane, UV resistance.